STRATEGY FOR IMPROVING THE COMPETITIVENESS OF SMES TOWARDS KOTALAMA BECOMING THE CENTER OF MALANG FRIED ONION INDUSTRY (International Conference of Graduate School on Sustainability (ICGSS), 2018)
The business of fried onions in Kotalama Village has been around for decades, making the surrounding community familiar with the ins and outs of processing fried onions. In its development Small and Medium Enterprises (SMEs) fried onions in Kotalama Village have problems to maintain and develop business. The problems faced are almost the same as other Small and Medium Enterprises (SMEs), namely the problem of Marketing, capital, production and human resources. To improve existing businesses and overcome more specific problems in the business of fried onions in Kotalama Village, Malang City, it is necessary to know the strategies that are suitable and appropriate to the conditions of the region by taking into account the existing internal and external factors. Data collection techniques used in this qualitative research are in-depth interviews by face to face with the informant, by getting a complete picture of the topics studied. The informants in this study were 12 people consisting of: Onion business group, Malang City Cooperative and SMEs Office, Academics, Onion Entrepreneurs and the local community. Based on the weighting of Internal Factor Analysis System (IFAS) and External Factor Analysis System (EFAS) from the results of questionnaires and interviews, the priority of the strategy is based on a combination of strategies that have the highest to the lowest value. The most appropriate strategy to increase the business competitiveness of fried onions Kotalama Malang City is Weakness-Opportunity (WO) with the highest weight of 3.23. suitable strategies for this are: Always participate in SME product exhibition activities to inform the existence of SMEs Kotalama fried onions, Maintain security and harmony conditions among business actors so that togetherness in advancing fried onion business arises, Maintaining product quality quality to maintain market and increase market reach, Improving facilities or infrastructure in the environment including business land, making media information / promotional media such as leaflets, brochures, or other media in collaboration with the government including the SMEs and industry offices to introduce fried onion Kotalama products and assist capital with the provision or manufacture of microfinance institutions community-based in the fried onion business area.